2017
DOI: 10.1128/mcb.00347-16
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation of Ku80 by RNF126 Promotes Completion of Nonhomologous End Joining-Mediated DNA Repair

Abstract: Repair of damaged DNA is critical for maintenance of genetic information. In eukaryotes, DNA double-strand breaks (DSBs) are recognized by the Ku70-Ku80 heterodimer, which then recruits proteins that mediate repair by nonhomologous end joining (NHEJ). Prolonged retention of Ku70/80 at DSBs prevents completion of repair, however, with ubiquitylation of Ku80 having been implicated in Ku70/80 dissociation from DNA. Here, we identify RNF126 as a ubiquitin ligase that is recruited to DSBs and ubiquitylates Ku80, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…Because the DDR has multiple pathways involved, there are several genome maintenance regulatory factors that play both positive and negative roles depending on the stage, or these pathways regulate each other ( 1 , 2 ). The first scenario concerning the role of RNF126 in DNA repair has been reported previously ( 28 , 29 ). In this study, we focused on the DNA damage response steps prior to repair.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because the DDR has multiple pathways involved, there are several genome maintenance regulatory factors that play both positive and negative roles depending on the stage, or these pathways regulate each other ( 1 , 2 ). The first scenario concerning the role of RNF126 in DNA repair has been reported previously ( 28 , 29 ). In this study, we focused on the DNA damage response steps prior to repair.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, we identified and characterized RNF126 as a novel negative regulator of RNF168-mediated ubiquitination and 53BP1 focus formation after DNA damage. Previous studies revealed the role of RNF126 as a positive regulator of DSB repair by controlling the expression level of BRCA1 in homologous recombination and by its ubiquitin ligase function in NHEJ ( 28 , 29 ). These reports highlighted the positive regulation of RNF126 in DSB repair, and our study elucidates a novel regulatory function of RNF126 in the DDR.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of RNF138 ubiquitylation on Ku80 abundance at break sites appears to be independent of proteasome-mediated degradation. However, RNF8, SCF Fbxl12 , VCP-p97, and RNF126 have all been implicated in targeting Ku to the proteasome, and thereby shifting the balance of repair from NHEJ to HR (21)(22)(23)(24). The CRL4 E3 ubiquitin ligase, which contains either CUL4A or CUL4B, has additionally been implicated in removal of Ku via a ubiquitindependent mechanism that is also dependent on neddylation (25).…”
Section: Regulation Of Nhejmentioning
confidence: 99%
“…Ubiquitylated Ku70/Ku80 is then removed from chromatin in a VCP-dependent manner and targeted for degradation by the proteasome (van den Boom et al 2016). This allows for completion of NHEJ (Ishida et al 2017) or activation of end resection, thereby triggering the alternative DSB repair pathway of HR (Ismail et al 2015;van den Boom et al 2016). The FBXW7-associated cullin-RING ligase, on the other hand, regulates the recruitment of XRCC4 to DSB sites through its K63-linked ubiquitylation (Zhang et al 2016).…”
Section: Wwp2 Promotes Cnhejmentioning
confidence: 99%